Bird Species' Network Centrality Varies Differentially across Species within Their Climatic Niches - Moulatlet, Gabriel M; Dáttilo, Wesley; Kissling, W Daniel; Villalobos, Fabricio (The American naturalist, 2025)
AbstractUnderstanding how the functional role of species within seed dispersal networks varies across geographical and climatic gradients can reveal the drivers of network organization. Because bird-plant interactions differ depending on where these occur, species' centrality (a measurement of species importance in the networks) is expected to vary across species' geographic distributions. Using a global dataset of bird-plant seed dispersal networks, we applied a cross-random mixed effects model to evaluate the variation of 239 bird species' centrality within local networks across their occupied climatic conditions and in response to coexisting bird and plant diversities in those networks. Our model indicated that centrality did not vary significantly with the distance to the climatic niche centroid but increased with increasing bird diversity. However, by examining species' individual responses we found that centrality did vary with the distance to the climatic niche centroid: 43% of the evaluated species (102) showed a negative relationship (higher centrality closer to the climatic niche centroid), whereas 51% of species (122) showed a positive relationship (higher centrality farther from the climatic niche centroid). The effect of bird diversity on individual species' centrality covaried positively with that of plant diversity more than having opposite effects, regardless of the network's position within the climatic niche. Taken together, the variation in individual species' centrality within the occupied climatic conditions suggests the existence of areas where species achieve high centrality, which might form the substrate for evolutionary and ecological dynamics.